2021
DOI: 10.1101/2021.02.09.430458
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intranasal type I interferon treatment is beneficial only when administered before clinical signs onset in the SARS-CoV-2 hamster model

Abstract: Impaired type I interferons (IFNs) production or signaling have been associated with severe COVID-19, further promoting the evaluation of recombinant type I IFNs as therapeutics against SARS-CoV-2 infection. In the Syrian hamster model, we show that intranasal administration of IFN-α starting one day pre-infection or one day post-infection limited weight loss and decreased viral lung titers. By contrast, intranasal administration of IFN-α starting at the onset of symptoms three days post-infection had no impac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The IFN-pretreated animals that did become infected had only limited virus titers, indicating that IFN pre-treatment reduced viral transmission and the infectivity of treated animals (Hoagland et al, 2021). Meanwhile, treating hamsters with IFN-⍺ at 3 dpi, coincident with symptom onset, did not change clinical outcomes (Bessie `re et al, 2021). By contrast, when non-human primates were infected with SARS-CoV-2, it resulted in significant upregulation of IFN-I and -II expression in bronchoalveolar lavage (BAL) fluid and induced robust ISG expression in the lungs, indicating that non-human primates mount a stronger IFN response to SARS-CoV-2 infection than that observed in other animal models (Chandrashekar et al, 2020;Singh et al, 2021).…”
Section: Sars-cov-2 Induction Of Ifn Pathways In Vitromentioning
confidence: 96%
See 1 more Smart Citation
“…The IFN-pretreated animals that did become infected had only limited virus titers, indicating that IFN pre-treatment reduced viral transmission and the infectivity of treated animals (Hoagland et al, 2021). Meanwhile, treating hamsters with IFN-⍺ at 3 dpi, coincident with symptom onset, did not change clinical outcomes (Bessie `re et al, 2021). By contrast, when non-human primates were infected with SARS-CoV-2, it resulted in significant upregulation of IFN-I and -II expression in bronchoalveolar lavage (BAL) fluid and induced robust ISG expression in the lungs, indicating that non-human primates mount a stronger IFN response to SARS-CoV-2 infection than that observed in other animal models (Chandrashekar et al, 2020;Singh et al, 2021).…”
Section: Sars-cov-2 Induction Of Ifn Pathways In Vitromentioning
confidence: 96%
“…The infection of other animal models with SARS-CoV-2, including of hamsters, ferrets, and non-human primates, results in mild clinical disease, with a lethal infection only observed in aged hamsters (Selvaraj et al, 2021). The infection of hamsters and ferrets with SARS-CoV-2 does not result in an IFN-b response (Bessie `re et al, 2021;Blanco-Melo et al, 2020;Hoagland et al, 2021), although ISG15 expression was observed after infection and remained elevated to 8 dpi, by which time the virus had already fully cleared (Hoagland et al, 2021). These data indicate that non-classical, IFN-independent induction of ISGs occurred in these animals after SARS-CoV-2 infection.…”
Section: Sars-cov-2 Induction Of Ifn Pathways In Vitromentioning
confidence: 99%
“…Interestingly, Stat2 -/- (lacking both type I and III IFN responses) hamsters fail to control SARS-CoV-2 infection, whereas this infection is successfully controlled by Il-28r -/- (deficient for the type III IFN response only) animals [ 84 ]. Moreover, intranasal treatment with universal IFN-α within one to three days of infection can protect hamsters from severe disease [ 85 , 86 ].…”
Section: Type I Ifn Immunity In Animal Models Naturally Susceptible To Sars-cov-2mentioning
confidence: 99%
“…Moreover, as global efforts are underway to identify and develop new anti-viral and immunomodulatory therapeutics that reduce COVID-19 related hospitalization and deaths, need arises for the right timing (38). Indeed, early type I IFN treatment seemed to be critical for therapeutic success (39). However, prophylactic immunomodulation might not be feasible for most COVID-19 patients due to high costs and potential adverse events.…”
Section: Figurementioning
confidence: 99%